Letter from Sir Francis Leopold M'Clintock, March 23, 1869 ... - M'Clintock, Francis Leopold, Sir, 1819-1907 (University of Victoria Libraries, 2021)
Part of a collection of letters from Arctic explorers Admiral Sir Edward Belcher (1799-1877) and Admiral Sir Francis Leopold M'Clintock (1819-1907) who engaged in Arctic surveys and were associated with the search for Sir John Franklin. Belcher commanded the expedition to search for Franklin in 1852 and M'Clintock discovered remains of the expedition in May 1859. This letter is from Sir Francis Leopold M'Clintock KCB FRS, and is concerned with personal matters. ...